The Analisis Kritis: Kritikan dan Pujian atas Abu Hurairah - Ali Mohtarom Mohtarom (Fakultas Agama Islam Universitas Yudharta Pasuruan, 2023)
The discussion about Abu Hurairah seemed to never end, no doubt negative things were thrown at him because his achievements were so great that he even won the first position in the narration of the Prophet's hadith in certain disciplines compared to other prominent companions. A total of 5,374 (five thousand three hundred and seventy four) hadiths were recorded in Abu Hurairah's memory and memory. In this paper review, the authors conducted a qualitative research method using a literature and literature research approach. This paper will present a biography of the figure of Abu Hurairah, how his role in the transmission of hadith as well as a critical analysis of the controversies of criticism and praise addressed to him. The results of the author's analysis are the opinions put forward by various groups, both friends and great scholars, about Abu Hurairah as a friend who has extensive knowledge and the most history of hadiths and that Abu Hurairah is no longer doubted by Muslims as a hadith leader, this is more convincing than accusations criticism directed at him.